Numerical modelling of ice-front oscillations and ice-dam occurrence at Glaciar Perito Moreno, the Southern Patagonia Icefield - Lannutti, E.; Lenzano, M.G.; Durand, M.; Lo Vecchio, A.; Moragues, S.; Lenzano, L. (Cuadernos de Investigación Geográfica, 2020)
The present study conducts the design and development of a computational numerical model to describe the behavior of the seasonal oscillatory cycle of advance and recession of the Perito Moreno glacier, named MO-ACAR. Within its oscillatory behavior, in some years the glacier advances and reaches the Magellan Peninsula forming an ice-dam that break down due to the water pressure of the lake after a certain time. Thus, the main goal of the MO-ACAR model is to simulate the daily ice-front position of the glacier and the events occurrence of the ice-dam formation during 1994-2018 period. The model is calibrated and validated from an iterative optimization process, based on the maximization of correlation values and minimization of distance errors to the Magallanes Peninsula. The simulation of the ice-dam’s formation and the oscillation of the frontal position achieved high performance, reaching optimal correlation values (0.99) and small errors in the position (9.56 ± 13.94 m), respectively. The results show that glacier dynamics and ice-dam’s formation respond to different time-scales; whilst in short-, intermediate-term (daily seasonal scales), the occurrence depends as much on the characteristics of the event as on the phase and intensity of the previous event. On the contrary, in long-term periods (scales greater than one year), low-frequency modulation of the ice flow velocity, caused by variations in air temperature, controls the periods with the formation of ice-dams and free of them.